Hubungan Supply Chain Management (SCM) Terhadap Kinerja Perusahaan Kedai Upu Panam Kota Pekanbaru - Denisyah, Denisyah; Maharani, Evy; Dewi, Novia (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
The rapid development of retail stores in Indonesia has made competition between companies tighter. Product availability and economical selling prices are one of the things that make retail companies survive. Supply chain management is an extension and development of the concept and meaning of logistics management, logistics management plays a role in managing the flow of goods to consumers. Unavailability of stock items, excessive stock of goods and insufficient stock of goods are problems that Kedai Upu often faces. This is due to the ignorance of retailer management about the number of stock items in real time due to inaccurate information, the amount of stock that is not in accordance with the stock provision system. The research objective is to analyze the relationship between information sharing, long-term relationships, cooperation and integration processes on company performance Kedai Upu Panam Pekanbaru City. The research time was conducted from January to July 2023. This research uses a case study method with purposive sampling technique and uses 30 key informants. Data analysis using Spearman rank analysis and descriptive analysis. The results showed that there was a significant relationship between the variables of information sharing, long-term relationships, cooperation and integration processes on company performance.